(untitled) (Proceedings of the International Conference on Education, 2021)
Service quality is very important for every institution, especially the government institutions. However, the service quality of General Bureau employees at the Ministry of State Secretariat was not optimal. This is known by the fact that the services provided are not in accordance with the expectations and the service standard. Therefore, this research was conducted by researchers, to find out what variables can affect service quality. Based on the results of quantitative analysis, it is known that service quality is influenced by several variables, including organizational culture and empowerment. The purpose of this quantitative comparative-correlational research, using survey method, is to reveal the effects of organizational culture and empowerment in correlated to general bureau quality services, directly or indirectly, and to determine appropriate strategies to improve the quality of service. Data was gathered from 76 employees of the General Bureau at the Ministry of State Secretariat Republic of Indonesia. In the result of the research revealed that (1) the culture of an organization has a direct impact towards the quality of a service, (2) empowerment gives a direct positive impact on service quality, (3) culture of an organization also gives a direct impact on empowerment, (4) the culture of an organization through empowerment results a positive impact on service quality. It can be concluded that the variable that directly affects service quality is the variable of organizational culture with a path coefficient of 0.322, it means that an increasement in organizational culture will cause an increase in service quality. This study examines the quality of service and the factors that influence it from the variables of organizational culture dan empowerment that has never been done before both in the sample, research location and the methods used by the researcher. The results showed that a significant model for improving the quality of employee services at the General Bureau was by improving organizational culture, and the empowerment as an intervening variable.